2000
DOI: 10.3109/10428190009053556
|View full text |Cite
|
Sign up to set email alerts
|

Blastoschizomyces Capitatus Infection in Acute Leukemia Patients

Abstract: Blastoschizomyces capitatus (BC), a filamentous fungus of genus Trichosporum, is as an important opportunistic pathogen in the compromised host. Within the past 10 years, 47 cases of BC infection have been published. Most of the patients had acute leukemia (AL) or related disorders and had received chemotherapy treatment. Due to BC's resistance to currently used antifungal agents, this infection represents a therapeutic challenge and serious complication in the treatment of hematology malignancies. Here we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 10 publications
1
27
0
Order By: Relevance
“…Overall, our results confirm the findings of the 3 previous reports that included 12 patients with this infection [1,6,7]. Table 2 shows the results of these 3 previous reports, compared with those of our current study.…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…Overall, our results confirm the findings of the 3 previous reports that included 12 patients with this infection [1,6,7]. Table 2 shows the results of these 3 previous reports, compared with those of our current study.…”
Section: Discussionsupporting
confidence: 96%
“…Among the emerging yeast pathogens, Blastoschizomyces capitatus is a rarely described yeast that produces severe systemic infection in such patients. Until now, most reports of infection caused by B. capitatus have described only a single case, with only 3 previous studies describing 12 cases [1,6,7]. Here, we report the results of a retrospective study performed in 7 tertiary-care hospitals in Spain that reported у1 case of B. capitatus infection from 1992 through 2002.…”
Section: Twenty-six Cases Ofmentioning
confidence: 72%
“…As for the newer antifungal drugs, it is currently impossible to make any predictions of their clinical efficacy. The literature contains reports of only a few cases in which voriconazole or caspofungin was used as initial or salvage antifungal therapy (43,77,101).…”
Section: Discussionmentioning
confidence: 99%
“…Central venous catheter removal (if present) also seems to be an important aspect of treatment (9). Adjuvant therapies advocated by some include hematopoietic growth factors (10), gamma interferon (4), and granulocyte transfusions (8,11).…”
mentioning
confidence: 99%